Incidence and Impact of Ventilator Associated Multidrug Resistant Pneumonia in Patients with SARS-COV2 - Seife Yohannes; Zaki Ahmed; Rachel Schelling; Swaminathan Perinkulam Sathyanarayanan; Alexandra Pratt; Mathew P. Schreiber (Critical Care Research and Practice)
Introduction. Ventilator Associated Pneumonia (VAP) is associated with significant cost, morbidity, and mortality. There is limited data on the incidence of VAP, appropriate antibiotic timing, and the impact of multidrug resistant VAP in intubated Coronavirus disease-19 (COVID-19) patients. Methods. A retrospective study was conducted at 2 tertiary urban academic centers involving 132 COVID-19 patients requiring invasive mechanical ventilation (IMV). The epidemiology of VAP, the impact of prior empiric antibiotic administration on the development of Multidrug Resistant Organism (MDRO) infections, and the impact of VAP on patient outcomes were studied. Results. The average age of the patients was 60.58% were males, 70% were African-Americans and two-thirds of patients had diabetes, hypertension, or heart disease. The average Body Mass Index (BMI) was 32.9. Forty-one patients (27%) developed VAP. Patients with VAP had a significantly higher Sequential Organ Failure Assessment (SOFA) score prior to Intensive Care Unit (ICU) admission. Sixty percent received empiric antibiotics before initiation of IMV, mostly on hospital admission, and 81% received empiric antibiotics at the time of intubation. The administration of empiric antibiotics was not associated with a higher prevalence of VAP. The prevalence of VAP was 22 per 1000 days on ventilation. No difference in mortality was seen between VAP and non-VAP groups at 49% and 57% respectively (p=0.4). VAP was associated with increased ICU length of stay (LOS), 30 vs. 16 days (p<0.001), and longer hospital LOS 35 vs. 17 days (p<0.001). 40% of VAPs were caused by MDROs. The most common organism was Staphylococcus aureus (28%), with almost half (48%) being methicillin resistant Staphylococcus aureus (MRSA). Conclusion. VAP was a common complication of patients intubated for COVID-19 pneumonia. Most patients received empiric antibiotics upon the hospital and/or ICU admission. There was a 40% incidence of multidrug resistant pneumonia. Patients who developed VAP had almost twice as long hospital and ICU LOS.